Deleuze and architecture - Frichot, Hélène 1970-; Loo, Stephen (Edinburgh University Press, 2013)
Critiques the legacy and ongoing influence of Deleuze on the discipline and practice of architectureGBS_insertPreviewButtonPopup(['ISBN:9780748674640','ISBN:9780748674657','ISBN:9780748674664','ISBN:9780748674671']);This collection looks critically at how Deleuze challenges architecture as a discipline, how architecture contributes to philosophy and how we can come to understand the complex politics of space of our increasingly networked world. Since the 1980s, Deleuze's philosophy has fuelled a generation of architectural thinking, and can be seen in the design of a global range of contemporary built environments. His work has also alerted architecture to crucial ecological, political and social problems that the discipline needs to reconcile.Key Features15 essays by interdisciplinary scholars including John Rajchman, Elizabeth Grosz and Brian MassumiShows Deleuze's influence on the emerging biotechnological paradigm and new practices of participatory designEngages with contemporary approaches to the theory and practice of architecture to provide radical agendas for the practice of Deleuzian philosophyList of ContributorsKaren Burns, University of MelbourneDeborah Hauptman, Delft University of TechnologyAndrej Radman, Delft University of TechnologyMarko Jobst, University of GreenwichHélène Frichot, Royal Institute of Technology (KTH), SwedenBernard Cache, Independent architect and furniture designerMike Hale, Architect at ArchispaceKim Dovey, University of MelbourneCatharina Gabrielsson, Royal Institute of Technology (KTH), SwedenCameron Duff, Monash UniversityAndrew Ballantyne, Newcastle University, UKAdrian Parr, University of CincinnatiChris Smith, University of SydneyStephen Loo, University of TasmaniaSimone Brott, Queensland University of TechnologyDoina Petrescu, University of SheffieldConstantin Petcou, University of SheffieldAnne Querrien, University of Sheffield
Keywords: Deleuze, Gilles -- 1925-1995; Philosophy; ARCHITECTURE / General; Architecture and philosophy; Architecture -- Philosophy -- History -- 20th century; Architekturtheorie; Architektur; Aufsatzsammlung